(untitled) - Caughley, Graeme (Cambridge, Mass., USA, 1996)
This important reference examines the logic and methods for the diagnosis and treatment of species extinctions and declines. Balancing the issues of population dynamics and risk assessment against the effects of the real-world pressures of economics and legislation, the authors analyze the role of ecology in the survival of endangered species.
Keywords: Bảo tồn sinh vật,Conservation biology